2015
DOI: 10.1051/0004-6361/201424559
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional magnetic and abundance mapping of the cool Ap star HD 24712

Abstract: Aims. We present a magnetic Doppler imaging study from all Stokes parameters of the cool, chemically peculiar star HD 24712. This is the very first such analysis performed at a resolving power exceeding 10 5 . Methods. The analysis is performed on the basis of phase-resolved observations of line profiles in all four Stokes parameters obtained with the HARPSpol instrument attached at the 3.6 m ESO telescope. We used the magnetic Doppler imaging code 10, which allowed us to derive the magnetic field geomet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
5

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 30 publications
4
35
0
5
Order By: Relevance
“…These four stars are young objects with masses between 2.3 and 3.1 M . Rusomarov et al (2015) found a dipole field for HD 24712, which has a mass of 1.55 M and is likely to be much older than the other stars. Thus, it appears that our finding of magnetic field for HD 125248, which is significantly more complex than a dipole, supports the hypothesis that old (or less massive) Ap stars have predominantly dipolar fields with little structure on small scales.…”
Section: Summary and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These four stars are young objects with masses between 2.3 and 3.1 M . Rusomarov et al (2015) found a dipole field for HD 24712, which has a mass of 1.55 M and is likely to be much older than the other stars. Thus, it appears that our finding of magnetic field for HD 125248, which is significantly more complex than a dipole, supports the hypothesis that old (or less massive) Ap stars have predominantly dipolar fields with little structure on small scales.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…We performed this task with the MDI code invers10 introduced by and . In this study, we closely follow already established methodological practices that have been used in recent MDI studies (e.g., Rusomarov et al 2015;Kochukhov et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the full Stokes vector studies of bright Ap stars α 2 CVn and 53 Cam discovered small-scale horizontal contributions on top of large-scale dipole-like fields (Kochukhov et al 2004a;Kochukhov & Wade 2010;Silvester et al 2014). On the other hand, the four Stokes parameter analysis of the cool Ap star HD 24712 (Rusomarov et al 2015) found no significant departures from a purely dipolar topology.…”
Section: Introductionmentioning
confidence: 99%
“…Our poor (u, v) plane coverage prevents us from analyzing the angular diameter variation with respect to the baseline orientation, which is not penalizing since HD 24712 is a very slow rotator, as are Ap stars in general. Its v sin i is quoted to be 18 km s −1 in Royer et al (2002) and, more recently, 5.8 km s −1 in Glebocki & Gnacinski (2005), and its inclination i equals 120 • (Rusomarov et al 2015), therefore no photosphere flattening is expected to be detectable. Our radius estimation is thus not biased by the rotational effect.…”
Section: Chara/vega Observationsmentioning
confidence: 87%
“…Like all the Ap stars, it exhibits a strong large-scale organized magnetic field whose intensity is changing as the star rotates with a period of 12.46 days (Lüftinger et al 2008). The recent study of Rusomarov et al (2015) concludes that the magnetic field topology of HD 24712 has a dominant dipolar component with a very weak contribution from high orders. The authors derive a polar field strength B p = 3440 G, an inclination angle between the line of sight and the stellar rotation axis of i = 120 • , and an angle between the magnetic and rotation axes of β = 160 • .…”
Section: Introductionmentioning
confidence: 99%